2017
DOI: 10.18632/oncotarget.15630
|View full text |Cite
|
Sign up to set email alerts
|

CD163 as a marker of M2 macrophage, contribute to predict aggressiveness and prognosis of Kazakh esophageal squamous cell carcinoma

Abstract: M2 macrophages was domesticated by tumor microenvironment to produce some angiogenic molecules and protease, facilitating angiogenesis and matrix breakdown, promoting tumor invasive and metastasis. However, The function of M2 macrophages to progression of esophageal carcinoma, especially Kazakh esophageal carcinoma is still dimness. This study aims to investigate M2 macrophages correlated with matrix metalloproteinase-9 (MMP9) and microvessel density, and the role in the progression of Kazakh esophageal squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
112
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 38 publications
(38 reference statements)
6
112
4
Order By: Relevance
“…In the present investigation, to understand the association between the infiltration of M2 macrophages and metastasis of ESCC, relevant literatures were meta‐analyzed. To confirm in our own cases, the infiltration of M2 macrophages in ESCC was evaluated using immunohistochemistry with CD163, a well‐accepted specific surface marker of M2 macrophages . Meta‐analysis revealed that the infiltration of M2 macrophages was markedly associated with lymph node metastasis, clinical stage and T classification in ESCC.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present investigation, to understand the association between the infiltration of M2 macrophages and metastasis of ESCC, relevant literatures were meta‐analyzed. To confirm in our own cases, the infiltration of M2 macrophages in ESCC was evaluated using immunohistochemistry with CD163, a well‐accepted specific surface marker of M2 macrophages . Meta‐analysis revealed that the infiltration of M2 macrophages was markedly associated with lymph node metastasis, clinical stage and T classification in ESCC.…”
Section: Introductionmentioning
confidence: 93%
“…To confirm in our own cases, the infiltration of M2 macrophages in ESCC was evaluated using immunohistochemistry with CD163, a well-accepted specific surface marker of M2 macrophages. 6 Meta-analysis revealed that the infiltration of M2 macrophages was markedly associated with lymph node metastasis, clinical stage and T classification in ESCC. In our own cases, M2 macrophages were shown to be predominantly infiltrated in ESCC relative to normal controls.…”
mentioning
confidence: 98%
“…Macrophages comprise the most abundant population of immune cells in the TME and can undergo differentiation into functional phenotypes depending on the local tissue environment. Presence of M2 macrophages and a high ratio of M2/M1 macrophages in the TME have been reported to be clinically linked with poor prognosis in many types of cancers, including ESCC (Shigeoka et al, 2013;Hu et al, 2017). Presence of M2 macrophages and a high ratio of M2/M1 macrophages in the TME have been reported to be clinically linked with poor prognosis in many types of cancers, including ESCC (Shigeoka et al, 2013;Hu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these functional phenotypes, tumor-associated macrophages (TAMs) can either promote (M2 subtype) or prevent (M1 type) tumor progression (Zheng et al, 2017). Presence of M2 macrophages and a high ratio of M2/M1 macrophages in the TME have been reported to be clinically linked with poor prognosis in many types of cancers, including ESCC (Shigeoka et al, 2013;Hu et al, 2017). However, the mechanism by which M2 macrophages promote the malignant behaviors of cancer cells remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…M2 macrophages are activated by IL‐4 and IL‐13, and have anti‐inflammatory properties, by producing cytokines such as IL‐10 . Also, M2 macrophages express Arg1, cluster of differentiation 163 (CD163), and mannose receptor (CD206) .…”
Section: Macrophages and Skeletal Muscle Regenerationmentioning
confidence: 99%